2016
DOI: 10.1007/s10916-016-0581-7
|View full text |Cite
|
Sign up to set email alerts
|

Semantically Enriched Data Access Policies in eHealth

Abstract: Internet of Things (IoT) requires novel solutions to facilitate autonomous, though controlled, resource access. Access policies have to facilitate interactions between heterogeneous entities (devices and humans). Here, we focus our attention on access control in eHealth. We propose an approach based on enriching policies, based on well-known and widely-used eXtensible Access Control Markup Language, with semantics. In the paper we describe an implementation of a Policy Information Point integrated with the HL7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In order to achieve user access rights and user authentication, the security classes here give different access privileges to each user and this model is responsible for encryption key distribution [44]. The authors of [45] used a combination for an extensible mark-up language (XML) and attribute-based access control (ABAC), which is extensible access control markup language (XACML), to get advantages like role-based access control (RBAC) and policy implementation along with e-health data representation by XML. In [46], Shuo et al proposed a two-level access control mechanism which includes role-based access control in the first layer with an enhanced RBAC in the second layer, due to the weak features of RBAC.…”
Section: Non-crypto Techniquesmentioning
confidence: 99%
“…In order to achieve user access rights and user authentication, the security classes here give different access privileges to each user and this model is responsible for encryption key distribution [44]. The authors of [45] used a combination for an extensible mark-up language (XML) and attribute-based access control (ABAC), which is extensible access control markup language (XACML), to get advantages like role-based access control (RBAC) and policy implementation along with e-health data representation by XML. In [46], Shuo et al proposed a two-level access control mechanism which includes role-based access control in the first layer with an enhanced RBAC in the second layer, due to the weak features of RBAC.…”
Section: Non-crypto Techniquesmentioning
confidence: 99%
“…Several authors have identified major challenges of clinical DSSs which should be handled with zeal. One of the major challenges stated to evolve an efficient decision-making framework is the heterogeneous clinical data, its utilisation, and storage into repository [13]. Another keystone that needs serious deliberation is to observe 'privacy'.…”
Section: Related Workmentioning
confidence: 99%
“…One of these challenges reported is ‘privacy’ which has been treated by several authors and situations including telemonitoring [26]. Another cornerstone to be preserved is the eHealth related data, where its access [27] and storage are critical steps in this security chain. As users are being considered as the centre of eHealth systems, new ways of thinking should be considered in these environments as stated by Werlang et al [28] where a new digital signature scheme approach is defined.…”
Section: Introductionmentioning
confidence: 99%